Shield Tunnel Cutter Replacement Technology - Chen, Jian.; Min, Fanlu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book proposes the tool change methods for the excessive tool wear in the construction rules of shield tunnel construction in China. From the perspective of shield tunneling, atmospheric pressure tool change, pressure opening and tool change, and other special techniques, the tool change technologies are proposed. It highlights a number of tool-changing techniques and research and development work, including pressure-changing tools, tool-changing tools in the tool-cylinder arm, and cutter-tooth cutter inter-change since the beginning of the construction of the Nanjing Yangtze River Tunnel.
Introduction -- Cutting, Wear and Replacement of Cutting Tools During Shield Tunneling -- Conventional Cutterhead & Tool-Changing Under Normal Pressure Technology -- Normal Pressure Tool Change Technology Based on Basic Pressure and Changeable Knife Design -- Stabilization Technology and Tool Change Technology for Open Face with Pressure Open -- Other Special Tool Changing Techniques.
Keywords: Engineering geology; Geotechnical engineering; Transportation engineering; Traffic engineering; Fire prevention; Buildings Protection.; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Transportation Technology and Traffic Engineering; Fire Science, Hazard Control, Building Safety; Tunnels -- China -- Design and construction; Tunneling -- Equipment and supplies